Avaliação intraespecífica da composição química dos óleos essenciais das folhas de Croton argyrophyllus (Euphorbiaceae) - Araújo, Lidiane Gomes de (2019)
The genus Croton, one of the largest in the Euphorbiaceae family, has aromatic species that produce essential oils rich in monoterpenes and sesquiterpenes and phenylpropanoids. The essential oils synthesized by Croton species have been extensively studied because of their vast amount of substances and a broad spectrum of biological activities. The literature shows that Croton argyrophyllus, the target of this study, is used in folk medicine as a sedative and for heart problems, and the leaf essential oil has anti-inflammatory, antioxidant, cytotoxic, antinociceptive, insecticidal and gastroprotective activity, but the chemical composition variations. The present work aimed to investigate the chemical composition of the essential oils of the leaves of nine different specimens of Croton argyrophyllus, as well as to evaluate their antibacterial activity. Fresh leaves of nine specimens of C. argyrophyllus were extracted by hydrodistillation in a Clevenger dosing apparatus. The essential oils (OCA1 to OCA9) were analyzed by gas chromatography coupled to mass spectrometry (GC/MS) to identify the chemical composition. In addition, it analyzed by near infrared spectroscopy (NIR) in order to verify the similarity between the analyzed samples. GC/MS analysis presented that the oils are composed exclusively of sesquiterpenes, and the major compound for all oils was bicyclogermacrene (mean 38.42%), followed by (Z)-cariophilene (mean of 14.06%), epi longipinanol (mean of 9.78%) and germacreno B (mean of 9.10%). The epi-longipinanol is being reported for the first time for the essential oil of C. argyrophyllus leaves. The data obtained from the analysis by NIR spectroscopy and CG/MS were treated by PCA and HCA, and showed similarity of the chemical samples’ profile. The essential oils OCA1 to OCA9 did not show variability in relation to the major compound. However, the quantitative analysis shows a significant difference in relation to the minority compounds. Statistical analyzes made it possible to form three clusters: OCA1-6, OCA7-8 and OCA9. These three clusters were submitted to evaluation of the antimicrobial activity against Staphlococcus aureus and all presented strong bactericidal activity, and the OCA7 + OCA8 group was the most active.